Calculation of Compressible Flow Past a Joukowski Aerofoil Using Direct Boundary Element Method with Linear Element Approach - Mushtaq, M.; Shah, N.A.; Muhammad, G.; Khan, S.A.; Ari, S.; Anjam, Y.N. (Pakistan Journal of Nutrition, 2013)
In this study, the Direct Boundary Element Method (DBEM) is being applied to present solution for surface and ground water bodies which are important nutrition fluids. To calculate a steady, irrotational, inviscid compressible flow past a Joukowski aerofoil using Direct Boundary Element Method with linear element approach. The results obtained using this method has been compared with the analytical solutions for the body under consideration.